KOMPETENSI GURU RA DALAM EVALUASI PEMBELAJARAN DI RA MIFTAHUL HUDA NGENEP KARANGPLOSO KABUPATEN MALANG Tahun Ajaran 2019/2020 - Indah Anifatul Fitria; Anwar Sa’dullah; Yorita Febry Lismanda (UNISMA, 2020)
Purpose of this research is knowing problems of teacher competence on learning evalution in RA Miftahul Huda NgenepKarangploso Malang. The main problem is about how the teacher competence on learning evaluation in that school. To solve this problem, researcher try for description the competence that the teacher have especially competence in learning evaluation. From that way, researcher can get conclusion about teacher competence in that school. This research use qualitative descriptive method.